Academic Infrastructures as a Critical Success Factors for Business Process Re-engineering to Achieve Academic Performance of Higher Education Institutions in the Democratic Republic of Congo (DRC) - Jean Bosco Mukolo (Universal Journal of Educational Research)
The study reviewed academic infrastructures which is a critical success factor and component of Business Process Re-engineering (BRP) in enhancing quality to achieve academic performance of higher education institutions in the Democratic Republic of Congo. This is a desktop review of literature study. The study used content and discourse analysis techniques to examine the secondary data collected from different books, journals, and websites, published, unpublished thesis, Government and World Bank sources. The researcher found consistent evidence in the literature to demonstrate that there is a significant and positive contribution of academic infrastructures in achieving performance of higher education institutions. The findings provide a valuable insight into the multifaceted factors contributing to improving quality education to achieve academic performance. These factors include: 1) physical aspects of infrastructures (libraries, laboratories, desks, tables, toilets and classrooms); 2) IT related materials and equipment (computer labs, internets, e-learning challenging to name few; 3) Electricity related problem (unreliable and absence of electricity in most of the rural areas and urban cities). The study concluded that improving academic infrastructures is paramount important to improve quality education and therefore achieve performance. This is the question of death or survival of higher education institutions which will have a significant and positive impact on socio-economic, cultural and political development of the country. This research contributes to the ongoing debate by providing insights into the critical success factors of BPR that can improve processes and achieve organizational performance. The recommendations were made based on the findings of the study.